A Sustainability Analysis Of Coconut And Copra Farming In Tolangohula District, Gorontalo Regency - Suryani yani; Amelia Murtisari; Karlena Arsyad (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: to analyze the income of coconut and copra farmers and assess the sustainability of coconut and copra farming based on economic, social, environmental, and management dimensions in Tolangohula Distict, Gorontalo Regency. Methodology: The research employed with purposive sampling involving 50 respondents from Gandasari and Margomulyo Villages. Data were collected through structured interviews and analyzed using cost analysis, gross and net income calculations, and a Multi-Ascpect Sustainability Analysis approach. Results: show that the average household income of coconut and copra farmers is IDR 13.176.800, comparising IDR 3.831.800 from coconuts and IDR 9.345.000 from copra. The multi-aspect evaluation indicates that coconut and copra farming in the study area falls into the sustainable category across all analyzed dimensions. Novelty: of this research lies in the integrated use of a multi-aspect approach to assess the sustainability of coconut and copra farming at the household level an approach that is still rarely applied in the Gorontalo context. This study also provides an in depth understanding of the economic contribution of coconut and copra to the well being of local farmers. Conclusion: that coconut and copra farming in Tolangohula District has sustainable potential and is feasible to be developed as part of a local resource based and environmentally friendly economic strengthening strategy. Type of Paper: research article